Alleviation of Cadmium Stress in Rice Seedlings Inoculated with Enterobacter tabaci 4M9 (CCB-MBL 5004) - Saidu Abdullahi; Hazzeman Haris; Kamarul Zaman Zarkasi; Amir Hamzah Ghazali (Tropical Life Sciences Research, 2024)
The growth of crop plants is greatly affected by the increased toxicity of metals. Luckily, certain beneficial bacteria can potentially reduce the effects of metal stress and promote the growth of the host plants. Many species of bacteria were reported as heavy metal tolerant and plant growth promoting, with very little or no report available concerning Enterobacter tabaci as heavy metal tolerant plant growth promoting. The present study aimed to evaluate the potential of Cadmium (Cd) tolerant Enterobacter tabaci 4M9 (CCB-MBL 5004) to alleviate heavy metals stress and enhance the growth of rice seedlings grown under Cd stress conditions. Rice seedlings were grown in Yoshida medium supplemented with different concentrations of Cd and inoculated with 4M9. The results showed that the inoculum tested successfully reduced oxidative stress in the seedlings by reducing the electrolyte leakage (EL) and increasing catalase (CAT) and superoxide dismutase (SOD) activities in the inoculated seedlings compared to the control counterparts. The results also revealed a significant increase in plant growth, biomass, and chlorophyll content of inoculated rice seedlings compared to the control. In general, the Cd tolerant E. tabaci 4M9 confers heavy metal alleviation and thereby improves the growth and survival of rice seedlings under Cd stress conditions. Therefore, the findings stated the potential of 4M9 for alleviating heavy metal stress and promoting the development of inoculated rice seedlings if accidentally grown under Cd-contaminated conditions.